Thrombophilic risk factors and homocysteine levels in Behçet’s disease in eastern Spain and their association with thrombotic events - Ricart, José M; Vayá, Amparo; Todolí, José; Calvo, Javier; Villa, Piedad; Estellés, Amparo; España, Francisco; Santaolaria, Marisa; Corella, Dolores; Aznar, Justo (Thrombosis and Haemostasis, 2006)
Behçet’s disease (BD) is a chronic inflammatory disorder in which thrombosis occurs in about 30% of patients. The prothrombotic mechanisms are unknown. Thrombophilic defects and hyperhomocysteinaemia may be involved in the pathogenesis of thrombotic events, although results have been controversial. Moreover, no information is available on this issue for eastern Spain.We studied the prevalence of inherited and acquired thrombophilic risk factors in 79 patients with BD (43 men, 36 women) who had (n = 23) or did not have (n = 56) thrombosis, and in 84 healthy control subjects (42 men, 42 women). Risk factors examined were antithrombin, protein C and protein S levels, factor V Leiden, the prothrombin G20210A mutation, the methylenetetrahydrofolate reductase C677T polymorphism, and acquired thrombophilic risk factors, including anticardiolipin antibodies, lupus anticoagulant, and serum homocysteine levels. There were no differences between patients and controls in any of the parameters studied.When we studied BD patients with and without thrombotic events, the only thrombophilic defect that differed was the prothrombin G20210A mutation: Three out of 23 patients with thrombosis were carriers, compared with none of 56 patients without thrombosis (p = 0.022).Two of the three carriers developed catastrophic or recurrent thrombotic episodes; one wasa homozygous carrier of the G20210A prothrombin mutation and the other was doubly heterozygous for the G20210A prothrombin mutation and factor V Leiden. A meta-analysis demonstrated an association of factor V Leiden and prothrombin mutation with thrombosis in BD. When studies from Turkey were excluded from the meta-analysis, only the prothrombin G20210A mutation was associated with thrombosis.
Keywords: Behçet’s disease; hyperhomocysteinaemia; thrombophilic risk factors; thrombosis; meta-analysis